القيادة التحويلية ودورها في المشاركة المجتمعية بالتعليم في ضوء رؤية 2030 - المالكي, حصة بنت عوض عبد الله (Tasnim International Journal for Human, Social and Legal Sciences, 2024)
The research aimed to address transformational leadership and its role in community participation in education in light of Vision 2030. The study relied on the descriptive and analytical approach, and the questionnaire was applied to a sample of the study population of (216) educational leaders in general education schools in Taif in the Kingdom of Saudi Arabia. The study concluded that the role of transformational leadership in community participation in education in light of Vision 2030 in public education schools in Taif was significant. The study recommended the necessity of organizing training courses for school leaders on applying the transformational leadership style to achieve community participation in light of the Kingdom’s Vision 2030 in all stages of public education. The study suggested the necessity of conducting a study similar to this study on the role of the transformational leadership style to achieve community participation in light of the Kingdom’s Vision 2030 in areas Others in the Kingdom to disseminate the results.